Removal of a ring causing penile strangulation with dental high speed turbine - Qiang Zhu; Jing Wang (Urology Case Reports, 2022)
Penile strangulation is a rare emergencythat requires prompt evaluation and treatment to avoid disastrous consequences. A 33-year-old male presented to the emergency department with complaints of severe penile pain and swelling for 10 hours.Dental high speed turbine is an effective means to quickly remove plastic rings.This method can provide immediate relief with no issue of heat transfer.